The Behavioral Accounting Approach to Examining Modern Accounting Practices in the Industry 4.0 Era - Amril Amril; Helmy Syamsuri; Wardatul Wahidah. R (Asian Journal of Management Analytics, 2026)
This study aims to analyze modern accounting practices in the industry 4.0 era through a behavioral accounting approach. Digital transformation in accounting systems, such as the use of ERP and cloud-based reporting, not only brings technical changes but also creates dynamics in individual and organizational behavior that impact the quality of financial reporting. This study uses a qualitative approach with a case study design. Data were collected through in-depth interviews with financial managers, accounting staff, and internal auditors directly involved in the implementation of modern accounting systems, supported by relevant documentation. Data analysis was conducted through data reduction, thematic presentation of findings, and drawing conclusions by linking the research findings to behavioral accounting theory. The results indicate that attitudes toward technology, work motivation, organizational culture, professional ethics, and cognitive biases significantly influence the effectiveness of modern accounting practices.